2013
DOI: 10.1371/journal.pone.0072207
|View full text |Cite
|
Sign up to set email alerts
|

Plant SILAC: Stable-Isotope Labelling with Amino Acids of Arabidopsis Seedlings for Quantitative Proteomics

Abstract: Stable Isotope Labelling by Amino acids in Cell culture (SILAC) is a powerful technique for comparative quantitative proteomics, which has recently been applied to a number of different eukaryotic organisms. Inefficient incorporation of labelled amino acids in cell cultures of Arabidopsis thaliana has led to very limited use of SILAC in plant systems. We present a method allowing, for the first time, efficient labelling with stable isotope-containing arginine and lysine of whole Arabidopsis seedlings. To illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…A 9-h offset between TX and TL causes an asymmetric peak in the synthesis rate, and a 12-h offset can produce a plateau-like pattern. It is very challenging to measure protein synthesis rates empirically (Schwanhäusser et al, 2011), especially with enough precision to distinguish relatively small differences, and especially in plants, where the key technique, stable isotope labeling with amino acids, is just barely becoming more common (Lewandowska et al, 2013). This is why a simulation is useful.…”
Section: Translational Control Of Circadian Clock Mrnasmentioning
confidence: 99%
“…A 9-h offset between TX and TL causes an asymmetric peak in the synthesis rate, and a 12-h offset can produce a plateau-like pattern. It is very challenging to measure protein synthesis rates empirically (Schwanhäusser et al, 2011), especially with enough precision to distinguish relatively small differences, and especially in plants, where the key technique, stable isotope labeling with amino acids, is just barely becoming more common (Lewandowska et al, 2013). This is why a simulation is useful.…”
Section: Translational Control Of Circadian Clock Mrnasmentioning
confidence: 99%
“…Plants can synthesize all of the standard 20 amino acids, which would suggest that providing exogenous labeled amino acids may not work. One prior work using stable isotope labeling by amino acids (SILAC) in Arabidopsis cell culture confirmed that amino acid labeling would be problematic due to incomplete labeling (Gruhler et al, 2005), while another investigation of SILAC for proteomic applications in seedlings showed that the strategy may be viable, with high incorporations of labeled amino acids into proteins (Lewandowska et al, 2013). But even if this strategy is viable in some defined scenarios, given the high cost of SILAC reagents, this strategy will be of limited use in hydroponic systems and would not scale well to the measurement of older plants and larger species of agricultural importance.…”
Section: Label Selection For Protein Turnover Studiesmentioning
confidence: 99%
“…Pulsed stable isotope labeling by amino acids in cell culture was introduced to monitor de novo protein synthesis, but poor label incorporation has prevented it from being widely adopted in plant systems. Other differential proteomics techniques, including stable isotope labeling by amino acids in cell culture (Lewandowska et al, 2013), hydroponic isotope labeling of entire plants (Bindschedler et al, 2008), 13 CO 2 labeling (Chen et al, 2011), and isobaric tags for relative and absolute quantitation (Ge et al, 2013), have emerged in recent years as tools to probe in vivo protein synthesis in plants. Notably, multiplexed quantifications with techniques such as isobaric tags for relative and absolute quantitation are inherently problematic due to known interference problems when using ion trap sources (McAlister et al, 2014).…”
mentioning
confidence: 99%